Inorganic Ion Exchangers for Cesium Removal from Radioactive Wastewater. Issue 4 (2nd October 2018) - Figueiredo, Bruno R; Cardoso, Simão P; Portugal, Inês; Rocha, João; Silva, Carlos Manuel
Abstract : Ion exchange is a proven process for radioactive wastewater decontamination, where inorganic sorbents are ideal due to their thermal, chemical and radiation stability. This review focuses on the removal of Cs + by inorganic exchangers, viz. zeolites, titanosilicates, hexacyanoferrates metal oxides and hydrous metal oxides, bentonite/clays and the key family of ammonium phosphomolybdates (AMPs). The design of new selective composites is also addressed focusing on those based on AMPs, hexacyanoferrates and titanosilicates/zeolites. Future inorganic Cs + exchangers will encompass promising solids, like lanthanide silicates, sodium titanates and metal sulfides. The sensing ability derived from the photoluminescence properties of lanthanide silicates and the efficiency of layered gallium-antimony-sulfide materials in acidic and basic solutions disclose considerable potential for real applications. The ion exchange systems are discussed in terms of sorbent capacity and selectivity (with competitors), pH, temperature and solution salinity. The microscopic features of the exchangers and the associated mechanisms (e.g., pore size, counterions radii, dehydration energy of the ions, coordination environments in the solid exchanger, and site accessibility) are always used for interpreting the ion exchange behavior. On the whole, more than 250 publications were reviewed and a large compilation of data is provided in Supplemental Material.